ANTESEDEN KEPUASAN KERJA DAN PENGARUHNYA TERHADAP KINERJA APARATUR BADAN NARKOTIKA NASIONAL PROVINSI ACEH - Mohammad Nasir; Marbawi Marbawi; Ibrahim Qamarius (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to determine two antecedent variabels of job satisfaction and the impact on personil performance of National Narcotics Agency Aceh Province. The data used is the data by distributing questionnaires to 175 respondent of personil National Narcotics Agency Aceh Province. To analyze the data, the statistical analysis used structure equation modeling (SEM) and processed with the help of the application Amos. The variables measured include individual characterstic and work characteristic effect toward job satisfaction and then analysis of statistical test is individual characterstic, work characteristic and job satisfaction effect toward of Personil Performance of  National Narcotics Agency Aceh Province. The result job satisfaction variable  effect of partial mediated  on individual characterstic and work characteristic toward to Personil Performance of  National Narcotics Agency Aceh Province.